The −670G>A polymorphism in the FAS gene promoter region influences the susceptibility to systemic sclerosis. Issue 4 (29th April 2008) - Liakouli, V; Manetti, M; Pacini, A; Tolusso, B; Fatini, C; Toscano, A; Cipriani, P; Guiducci, S; Bazzichi, L; Codullo, V; Ruocco, L; Dell'Orso, L; et al.
Abstract : Objective: To evaluate the role of the single-nucleotide polymorphism (SNP) at position −670 in the FAS gene promoter ( FAS −670G>A) in influencing the susceptibility, clinical features and severity of systemic sclerosis (SSc). Methods: 350 white Italian SSc patients (259 with limited cutaneous SSc (lcSSc) and 91 with diffuse cutaneous SSc (dcSSc)) and 232 healthy individuals were studied. Patients were assessed for the presence of autoantibodies (anticentromere, anti-topoisomerase I (anti-Scl-70) antibodies), interstitial lung disease (ILD), pulmonary arterial hypertension and scleroderma renal crisis. FAS −670G>A SNP was genotyped by PCR restriction fragment length polymorphism assay. Serum levels of soluble FAS (sFAS) were analysed by ELISA. Results: A significant difference in FAS −670 genotype distribution was observed between SSc patients and healthy individuals (p = 0.001). The frequency of the FAS −670A allele was significantly greater in SSc than in controls (p = 0.001). No significant difference in genotype distribution and allele frequencies was observed between lcSSc and dcSSc, although a greater frequency of the FAS −670A allele was found in dcSSc. The FAS −670AA genotype significantly influenced the predisposition to SSc (OR 1.97, 95% CI 1.35 to 2.88, p = 0.001) and to both lcSSc (OR 1.84, 95% CI 1.23 to 2.75, p = 0.003) and dcSSc (OR 2.37, 95% CI 1.41 to 3.99, p = 0.001). FAS −670A allele frequency was greater, although not significantly, in anti-Scl-70 antibody-positive dcSSc and ILD dcSSc. sFAS was significantly higher in patients and controls carrying the FAS −670AA genotype compared with those carrying the FAS −670GG genotype (p = 0.003 in SSc, p = 0.004 in controls). Conclusion: The FAS −670A allele is significantly associated with susceptibility to SSc, suggesting a role for a genetic control of apoptosis in the pathogenesis of the disease.